A case of spleen hydatid cyst - El Brahmi, Yasser; Anajjar, Mohamed; Rebbani, Mohammed; Ehirchiou, Abdelkader; Ait Ali, Abdelmounaim (International Surgery Journal, 2020)
The hydatid cyst of the spleen results from the development of the hydatid worm Echinococcus granulosus, in the splenic parenchyma. Humans are the accidental intermediate host in the development cycle of hydatid disease. Splenic involvement is the third most common location after the liver and lung. Echography and sometimes tomography are needed to confirm the diagnosis. In the absence of truly effective medical treatment, splenic hydatidosis often leads to surgery. Resection of the protruding dome is the treatment of choice due to low morbidity and absence of mortality. We report the case of 27 years old, with no particular medico-surgical history, referred to our hospital for the treatment of a splenic hydatid cyst discovered fortuitously during a radiological assessment. The patient was operated by laparoscopy. The treatment consisted of sterilization of the contents of the cyst with hydrogen peroxide, removal of the contents and resection of the salient dome, the results were unremarkable.